Helm - Hall, Sarah, 1974- (Mariner Books, 2025)
Helm is a ferocious wind, part elemental god, part aerial demon blasting through the landscape of Northern England since the dawn of time. But now Dr. Selima Sutar fears human pollution is killing Helm.